Determinants of national health insurance enrolment among people at risk of statelessness in the Awutu Senya East Municipality and Gomoa East District of Ghana - Theophilus Quartey; Charles Peprah; Anthony Kwame Morgan (BMC, 2023)
Abstract Background This paper investigates the factors influencing the decision to enrol in Ghana's National Health Insurance Scheme (NHIS) among people at risk of statelessness, with emphasis on the individual's demographic and socioeconomic factors.  Methods The study used data from a cross-sectional household survey undertaken in the Awutu Senya East Municipality and Gomoa East District of Ghana's Central Region between March 9 and June 26, 2021, on healthcare utilization culture among people at risk of statelessness. Descriptive statistics and binary logistic regression were used in analysing data from a sample of 384 people at risk of statelessness.  Results The results reveal that about 51% of the at-risk population have ever enrolled while 48% of the respondents were enrolled on the NHIS at the time of the survey (active members). The majority of the enrolled members acquired their membership through self-payment of the enrolment fee. Additionally, respondents aged 26-35 had higher odds of enrolling, whiles those within 56-65 years had lower odds of enrolling in health insurance. Also, persons who are married and have a high school education or an equivalent qualification were more likely to enrol, while persons with no employment were less likely to enrol. Conclusion According to the paper, while the gap in coverage between rich and poor, married and single appears to have narrowed, these factors continue to determine NHIS coverage among people at risk of statelessness. The same is true for education. Efforts must be increased to ensure equal access to healthcare financing interventions for better access to health services.